Review of selective accumudation of photosensitizers with different chemical structure in tumor tissue - E. A. Machinskaya; V. I. Ivanova-Radkevich (Biomedical Photonics, 2013)
The review of available theories explaining mechanisms of photosensitizer selective accumulation in tumor tissue is represented in the article. Variants associated with both targeted delivery of compounds with different chemical structure to tumor and low elimination rate of photosensitizers in the tumor are described. Details of tumor cell up-take of photosensitizer bounded with lipoproteins due to increased expression of low solidity lipoproteins receptors comparing with normal cells; mechanisms of photosensitizer accumulation in tumor tissue due to phagocytosis by macrophages localized in this area; mechanisms of binding of porphyrin-based photosensitizer by collagen fibers, production of which is increased in tumor cells, and other mechanisms are reviewed. Perspectives of practical application of knowledge about mechanisms of selective accumulation for induced increase in selectiveness of photosensitizer accumulation in tumor through targeted delivery of agent to pathological tissues are shown. Analysis of world trends in the search of transport systems for photosensitizers is performed.